Trends in Breast, Colorectal, and Cervical Cancer Incidence Following the Affordable Care Act: Implications for Cancer Screening - Sun, Maxine (JAMA Oncol, 2017)
This observational study uses incidence rates before and after adoption of the Affordable Care Act (ACA) to assess whether adoption of the ACA increased screening for breast, colorectal, and cervical cancer.